Distributional effects of exchange rate depreciations: Beggar-thy-neighbour or beggar-thyself? - Boris Fisera (Charles University in Prague, Institute of Economic Studies (IES), 2023)
While it is often argued that exchange rate depreciation has a beggar-thy-neighbour effect, in this paper, we investigate, whether exchange rate depreciation has a beggarthyself effect. Specifically, we explore the distributional consequences of Exchange rate movements. Using a heterogeneous panel cointegration approach, we find that, on average, small depreciations of the domestic currency decrease income inequality over the long-term. However, large depreciations in excess of 25%, increase income inequality over the long term. Large appreciations of the domestic currency also increase income inequality. Next, we identify 119 episodes of managed depreciations to better capture the distributional consequences of exchange rate movements. Managed depreciations are defined as situations in which the central bank intervenes to depreciate its domestic currency. Using the local projections (LP) approach, we find that managed depreciation shocks decrease income inequality. We find no evidence supporting the idea that exchange rate depreciation has a 'beggar-thyself' effect with respect to income inequality, as it does not seem to increase inequality.
Keywords: F10; F30; F31; F43; 330; exchange rate depreciation; income inequality; competitive devaluation; managed depreciation; distributional effects